Body data—data body: Tracing ambiguous trajectories of data bodies between empowerment and social control in the context of health - Mager, Astrid; Mayer, Katja (Momentum Quarterly, 2019)
A plethora of health apps and tracking devices is used around the globe to measure, store, and process body data. In this article, we use various approaches from the fields of science and technology studies (STS), surveillance studies and medical sociology to grasp and theorize these global trends of body datafication in health-related contexts. We (re)introduce the post-digital concept of the data body as the intersection of online and offline, individual and collective, private and public aspects, emphasizing the entanglements of the physical body from its data-dimensions and its situatedness between empowerment and social control. We conclude by discussing aspects of ownership, care, and control of digital data bodies and how both individuals and society may cope with them in the future.